IMPROVING KNOWLEDGE AND EMPOWERMENT OF PITASIDIA HEALTH CADRES ABOUT MEDICINAL PLANTS IN PATIENTS WITH DIABETES MELLITUS AND HYPERTENSION IN SINGOTRUNAN VILLAGE, BANYUWANGI SUB-DISTRICT, BANYUWANGI DISTRICT - Mustika, Arifa; Fatimah, Nurmawati; Herisulistyo, Aldilatama; Dau, Daniel (Universitas Airlangga, 2024)
Hypertension (HT) and Diabetes Mellitus type 2 (DM2) are the two most common non-communicable diseases in East Java, Indonesia. Therefore, there is a need for outreach about these two diseases and the use of herbal plants as complementary therapy. educational and learning practices are needed to be able to understand these two diseases and be able to make good herbal preparations such as Centella asiatica and Hibiscus sabdariffa so that the chemical compounds are not damaged. To provide education about HT and DM, herbal plant processing practices, and understanding the importance of regular health checks. The activity was conducted in Singotrunan Village, Banyuwangi Sub-district, Banyuwangi Regency, East Java Province. The stages of community service consist of preparation, implementation, and evaluation. The evaluation results showed that there was a 90% increase in the level of understanding after providing education on DM prevention, HT, and medicinal plants. Routine health checks found that most of the correspondents had random blood glucose levels and normal blood pressure. There was an increase in respondents' knowledge about hypertension and diabetes mellitus and the use of medicinal plants in helping the treatment of these diseases.